SOSIALISASI TES KEMAMPUAN AKADEMIK (TKA) SEBAGAI UPAYA MENINGKATKAN KESIAPAN SISWA KELAS VI SEKOLAH DASAR - Fanisa Dina Amalia Dewi Umbara; Avianti Permata Yuniar; Dinar Nirmalasari (SEBA: Jurnal Pengabdian kepada Masyarakat, 2026)
Academic Ability Test (Tes Kemampuan Akademik/TKA) was introduced as an assessment to measure students’ individual academic achievement. The successful implementation of TKA strongly depends on the readiness of teachers and students to understand the objectives, characteristics, and structure of the assessment. This community service activity aimed to improve elementary school students’ and teachers’ understanding of TKA through a socialization program. The activity was conducted at SDN Cerocoh, Serang Regency, involving 25 sixth-grade students. A one group pretest-posttest design was employed. The data were analyzed using descriptive quantitative analysis by calculating the mean scores and N-Gain to determine the improvement in participants’ understanding, while a Likert-scale questionnaire was used to examine participants’ responses to the activity. The results indicated an increase in participants’ knowledge and highly positive responses toward the socialization program. These findings suggest that TKA socialization is effective in enhancing participants’ understanding and providing a positive learning experience, indicating its potential for sustainable implementation. Keywords: Elementary School; Socialization; Academic Ability Test